DINAMIKA IMPLEMENTASI KURIKULUM PENDIDIKAN DASAR DALAM MENGHADAPI PERMASALAHAN PENDIDIKAN - Mayang Ismaya; Hadiyanto; Eka Sastrawati; Yantoro (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The implementation of Kurikulum Merdeka in Indonesia faces significant challenges, particularly in areas with limited infrastructure and human resources (HR). This study aims to identify the challenges in the implementation of Kurikulum Merdeka, focusing on the quality and distribution of teachers, technology limitations, and infrastructure disparities in remote areas. The research methodology used is descriptive qualitative, with data collection through interviews, observations, and documentation related to the implementation of the curriculum. The results of the study show that many teachers still struggle to integrate technology due to limited training and access to digital devices. Furthermore, the disparity in the distribution of trained teachers between urban and rural areas causes the quality of education in remote areas to be unequal to that in urban areas. Limited infrastructure, including poor internet access, further exacerbates this gap. Therefore, the study recommends the need for continuous training for teachers, improvement of education infrastructure, and the equal distribution of technology access throughout Indonesia to optimize the implementation of Kurikulum Merdeka and improve the quality of education equally across the country.